2018
DOI: 10.3906/biy-1804-35
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomic characterization and bioactivity of Protoiurus kraepelini (Scorpiones: Iuridae) venom

Abstract: Protoiurus kraepelini is a scorpion species found in parts of Turkey and Greece. In this study, the peptide profile of its venom was determined for the first time. The electrophoretic profile of the crude venom showed a protein distribution from 2 to 130 kDa. MALDI-TOF MS analysis of the venom peptide fraction yielded 27 peptides between 1059 and 4623 Da in mass. Several ion channelblocking and antimicrobial peptides were identified by peptide mass fingerprinting analysis. Cytotoxic and antimicrobial effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The toxin-families found in P. kraepelini in this study are congruent with other studies which also found both ion-channel targeting toxins and enzymatic NDBP toxins [32].…”
Section: Discussionsupporting
confidence: 92%
“…The toxin-families found in P. kraepelini in this study are congruent with other studies which also found both ion-channel targeting toxins and enzymatic NDBP toxins [32].…”
Section: Discussionsupporting
confidence: 92%